25 Years of Ed Tech, 2020 By Martin Weller. Athabasca University Press. - Brenna Clarke Gray (The Canadian Network for Innovation in Education (CNIE), 2021)
Martin Weller's 25 Years of Ed Tech is a necessary - and surprisingly fun! - review of the technologies, practices, pedagogies, and historical amnesias that have created (and plagued) the field of educational technologies for the last two and a half decades. In tracing the major technological developments, Weller also outlines the trends that shape these developments, and suggests some rules for good practice as we look towards a future where technology-enabled learning is almost certainly the norm, if not the default.